Analisis Kelayakan Ekonomi Islam Melalui Investasi Mesin CNC Pada Industri Manufaktur Menengah Dengan Pendekatan Net Present Value (NPV) - Supriono Supriono; Nur Asyiah Siregar; Risky Fajar Sundari; Rena Arifah; Riza Ria Wirasari (Journal of Computer Science and Information System(JCoInS), 2026)
This article aims to analyze the economic feasibility of CNC machine investment in a medium-sized manufacturing industry using the Net Present Value (NPV) approach. The research method used is a library search, which involves collecting and analyzing secondary data from literature related to CNC machine investment, feasibility studies, and NPV calculation methods. The analysis begins with identifying initial investment costs, projecting annual net cash flows, determining the discount rate, calculating the NPV, and analyzing sensitivity to changes in key variables. The results show a positive NPV, indicating that this investment is financially profitable and feasible. In addition to financial benefits, the use of CNC machines also provides strategic benefits such as increased production efficiency, reduced reject rates, and improved product quality. Therefore, investing in CNC machines is recommended as a strategic step to increase the competitiveness and productivity of medium-sized manufacturing industries amidst increasingly fierce market competition.